(untitled) (Al-Academy, 2025)
The senses play a pivotal role in artistic creativity, serving as a primary means of receiving impressions and transforming them into complex visual and sensory experiences. This study aims to explore how the senses, particularly the sense of smell, are employed in contemporary arts as an entry point for artistic expression. The study relies on a historical analysis of the role of the senses in art, tracing their evolution across different eras until scents began to be used as an expressive tool in modern artistic practices. The study discusses artistic practices that have incorporated scents into artworks and how this has contributed to enhancing sensory and aesthetic interaction between the audience and the artwork. It also examines the significance of scents in evoking memories and enhancing emotional engagement in the arts. The study raises key questions about how the senses have been present throughout history, their impact on artistic expression, and the role of smell in contemporary art. The study aims to analyze artistic practices that have utilized the senses—particularly scent—to shape a unique sensory experience. The significance of the study lies in highlighting the aesthetic and symbolic value of scents and their role in developing contemporary art concepts, opening new horizons for creativity and artistic interaction.